All roads lead to power : the appointed and elected paths to public office for US women - Sidorsky, Kaitlin N. (Studies in government and public policy., 2019)
"We are accustomed to hearing about a gender gap in politics. The low representation of women in elected office is well-documented and typically attributed to institutional barriers, discrimination, and differences in political ambition due to socialized gender norms. The problem with this narrative, as Kaitlin Sidorsky observes, is that it leaves out political appointment as an alternative path to public service. More women participate in politics than scholars have acknowledged, but they do so through appointments. And this road to power has been understudied for the same reason that many women pursue appointed positions over elected office: because they can serve the public in a way that does not seem "political." Women are not always just "victims" of their own lack of self-confidence or a biased political sphere, but in fact make a conscious decision to enter politics through what they consider a far less partisan and negative entry point. Very few scholars have studied female appointees in the same manner they study female officeholders, and this omission ignores the political histories, recruitment patterns, and levels of political ambition of women. It also underappreciates the importance of appointed positions, which are some of the most important roles in the government. All Roads Lead to Power explores why women are attracted to these positions through an original survey and interviews with officials across twenty states and four bureaucratic departments. Sidorsky's research sheds light on the recruitment process, motivations for holding office, and political ambitions of women who look for alternative, "non-political" routes to public service"--